Functional tuning of Vascular L-type Ca2+ channels - Mironova, Galina Yu; Haghbin, Nadia; Welsh, Donald G. (Frontiers in Physiology, 2022)
Vascular smooth muscle contraction is intimately tied to membrane potential and the rise in intracellular Ca2+ enabled by the opening of L-type Ca2+ channels. While voltage is often viewed as the single critical factor gating these channels, research is starting to reveal a more intricate scenario whereby their function is markedly tuned. This emerging concept will be the focus of this three-part review, the first part articulating the mechanistic foundation of contractile development in vascular smooth muscle. Part two will extend this foundational knowledge, introducing readers to functional coupling and how neighboring L-type Ca2+ channels work cooperatively through signaling protein complexes, to facilitate their open probability. The final aspect of this review will discuss the impact of L-type Ca2+ channel trafficking, a process tied to cytoskeleton dynamics. Cumulatively, this brief manuscript provides new insight into how voltage, along with channel cooperativity and number, work in concert to tune Ca2+ responses and smooth muscle contraction.